Analysis of Agreements on Mekaar Product Financing by PT Permodalan Nasional Madani from the Perspective of Islamic and Civil Law - Karimatul Khasanah; Nirmala Amary Hidayat (Journal Of Legal Studies Judex Praetor, 2025)
Mekaar is a financing program for underprivileged women based on a group savings and loan system, implemented through contractual agreements between PT Permodalan Nasional Madani (PNM) and its clients. In legal theory, a contract is valid if it fulfills the essential elements and conditions, adheres to contractual principles, and is free from legal prohibitions. However, the Mekaar financing practice has not fully met these requirements, raising legal issues that require further examination. This study aims to analyze the Mekaar financing agreement at PT PNM in Randudongkal District, Pemalang Regency, from the perspectives of Islamic law and civil law. The research employs an empirical juridical method with conceptual and statutory approaches. Primary data were obtained through interviews with clients and PNM officers, while secondary data came from literature, journals, previous theses, and relevant legislation. The results indicate that from the perspective of Islamic law, the Mekaar agreement is valid in terms of parties (aqidain) but weak in the elements of offer and acceptance (ṣigat), object (maḥallul ‘aqd), and purpose (mauḍū‘ al-‘aqd). The practice involves gharar, riba, and violations of transparency and justice principles, such as initial deductions, hidden interest, and lack of contract copies. From a civil law perspective, the Mekaar contract constitutes a loan agreement but does not fully satisfy Article 1320 of the Civil Code, potentially rendering it voidable and weakening legal protection for the parties.